Peran Tujuan Pendidikan sebagai Arah dan Dasar Komponen Utama Kurikulum - A. Hilwa Syauqy Mazidah; Dwi Tantri Indrajita; Muhamad Kenzie Zuhdi Ariqo (Jurnal Pendidikan, Bahasa dan Budaya, 2026)
Curriculum is the core of the educational process, yet in practice, its structural components often operate in isolation from their overarching goals. While the curriculum drives the educational process, its practical application often suffers from a disconnect between individual components and overarching objectives. This study explores the vital function of educational goals in directing and grounding core curricular elements. Through qualitative literature-based research, data were extracted from both foundational and contemporary curriculum theories, journals, and relevant texts, followed by systematic reduction, conceptual analysis, and integration. The analysis reveals that educational goals are pivotal mechanisms not just paperwork that harmonize content choice, teaching strategies, and assessment models into a unified framework. Vaguely defined goals inevitably weaken the functionality of these dependent elements. Ultimately, this research underscores the need for educators and curriculum architects to use educational goals as a strict blueprint to bridge the divide between theoretical philosophy and classroom execution.